Spirituality, Identity and Education - Jarosław Marzec (University of Lower Silesia, 2012)
Presented text tends to describe crucial issues of selfrealisation society. For the author there was important to show the specific of temporary culture called therapeutic culture and to grasp some of the important moments of the culture of individualism. To come out from the late works of Michel Foucault author follows how the imperative of our times to " take responsibility for the self-creation" has come out. Besides of drawing the genealogy of individualism culture text tends also into direction to show the possibilities of use the humanistic technology of self on the example of Ken Wilber's concept of Integral Life Practice. I argue to use this conception to build the theoretical frame for the inquiry of contemporary andragogy. In the ending section of the text author indicate important trail in the search for the pedagogical discourse of humanistic psychology. The intention tends to describe the issue how the language of humanistic psychology is subdued by the human resources discourse.